Hedging Game Contingent Claims with Constrained Portfolios (Advances in Applied Mathematics and Mechanics, 2018)
Game option is an American-type option with added feature that thewriter can exercise the option at any time before maturity. In thispaper, we consider the problem of hedging Game Contingent Claims(GCC) in two cases. For the case that portfolio is unconstrained, weprovide a single arbitrage-free price $P_0$. Whereas for theconstrained case, the price is replaced by an interval$[h_{low},h_{up}]$ of arbitrage-free prices. And for the portfoliowith some closed constraints, we give the expressions of theupper-hedging price and lower-hedging price. Finally, for a specialtype of game option, we provide explicit expressions of the priceand optimal portfolio for the writer and holder.